Effect of amino acids and peptides on growth of pediococcus pentosaceus from wine - Aredes Fernández, Pedro Adrián (2003)
Lactic acid bacteria are characterized by numerous nutritional requirements. The influence of amino acids and peptides on the growth of Pediococcus pentosaceus c1 isolated from argentinean wines was determined. Cells were growth in synthetic media and in the same media added with the following dipeptides: leucine-leucine; leucine-proline; methionine-proline and glycineglycine. In the complete medium, P. pentosaceus c1 reached a final biomass of 1x10(8) 6.5pt. When leucine, methionine and glycine were independently removed from complete medium, cell biomass was lower than 90% indicating that these amino acids are essentials to bacterial growth. In absence of proline the parameters of growth were similar to those obtained on control medium, indicating that proline was not essential for bacterial growth. The growth was partially restored in the medium without methionine (80 %), after addition of the dipeptide methionine proline, and a growth of 90 % was reached by the addition of leucine-proline to the medium without leucine. When leucine-leucine was added to the medium without leucine, 100 % of cell growth was observed and when glycine-glycine was incorporated to the medium without glycine, growth parameters were increased. Dipeptides could supply the essential amino acid requirements of P. pentosaceus c1. The lower specific growth rate (20 %) and cell biomass (70 %) obtained when the four dipeptides were added to the medium without leucine, methionine, glycine and proline, suggest that a limited uptake of amino acids by P. pentosaceus c1 could be caused by a substantial concentrations of dipeptides.